2018
DOI: 10.1002/jcp.26902
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA H19 inhibits abnormal differentiation of small intestinal epithelial cells in diabetic mice

Abstract: Diabetes mellitus (DM) comprises a group of metabolic diseases characterized by insulin deficiency or resistance and hyperglycemia. We previously reported the presence of abnormal differentiation of small intestinal epithelial cells (IECs) in diabetic mice, but the exact mechanism of this phenomenon has not been thoroughly elucidated to date. In this study, we found that H19 was markedly upregulated in IECs of DM mice. H19 knockdown significantly inhibited abnormal differentiation of IECs in DM mice. Bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…lncRNA MIAT upregulates the TGFβ1 signaling pathway and enhances diabetic retinopathy [7]. In diabetic mice, the downregulation of lncRNA H19 suppresses the abnormal differentiation of small intestinal epithelial cells by competing with miR-141-3p [8]. The knockdown of HOTTIP regulates the cell cycle and insulin secretion by suppressing MEK/ERK axes in islet β cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA MIAT upregulates the TGFβ1 signaling pathway and enhances diabetic retinopathy [7]. In diabetic mice, the downregulation of lncRNA H19 suppresses the abnormal differentiation of small intestinal epithelial cells by competing with miR-141-3p [8]. The knockdown of HOTTIP regulates the cell cycle and insulin secretion by suppressing MEK/ERK axes in islet β cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Given the crucial roles in differentiation in IECs, examination of Rspo3 mechanism has provided new insight into the regulatory roles in stem cell behavior. Many studies have demonstrated miRNAs take part roles in differentiation of IECs in the mouse [14,25,26].Through miRNA expression pro les, bioinformatic analysis, and RT-qPCR, we noticed a miRNA, miR-380-5p, which was downregulated in IECs tissues. In addition, by an in situ hybridization of a DIG-labeled LNA-miR-380-5p probe, we found that distribution of miR-380-5p is consistent with Rspo3.…”
Section: Discussionmentioning
confidence: 81%
“…In our previous research, we found that the Wnt/β-catenin signaling pathway was continuously activated in IECs of DM mice [14], and the reason why Wnt/β-catenin pathway continuously was activated, and still need further study. In IESCs, the Wnt pathway is essential for intestinal crypt formation and renewal, whereas Rspo-mediated signalling mainly affects ISC numbers [20].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations